Aetiology, diagnosis and treatment of posterior cross-bites in the primary dentition - M. MALANDRIS & E. K. MAHONEY (Paediatric Dentistry, 2004)
Recognizing conditions which predispose young children to malocclusions is an important part of any comprehensive paediatric dental assessment.